2012
DOI: 10.6004/jnccn.2012.0087
|View full text |Cite
|
Sign up to set email alerts
|

Exocrine Pancreas Cancer and Thromboembolic Events: A Systematic Literature Review

Abstract: Exocrine pancreas cancer continues to represent a significant therapeutic challenge, with high rates of mortality and morbidity, including from thromboembolic events, which have long been described as a frequent complication of the disease. This article provides a systematic and comprehensive review of the literature to address the clinical and pathologic features recognized in pancreas cancer pertaining to thrombosis, and to discuss ongoing investigations of prophylactic anticoagulation in the hopes of improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 66 publications
(79 reference statements)
0
14
0
2
Order By: Relevance
“…It is estimated to be responsible for more than a quarter of a million deaths and be the fifth leading cause of cancer death in worldwide (Epstein et al, 2012). The prognosis is extremely poor, with 5-year survival rate of less than 5% even with the surgical and chemotherapy intervention (Le Scodan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated to be responsible for more than a quarter of a million deaths and be the fifth leading cause of cancer death in worldwide (Epstein et al, 2012). The prognosis is extremely poor, with 5-year survival rate of less than 5% even with the surgical and chemotherapy intervention (Le Scodan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The role of prophylactic anticoagulation in this patient population is an area of active debate . In the CLOT trial (Comparison of Low‐Molecular‐Weight Heparin Versus Coumadin for the Prevention of Recurrent Venous Thromboembolism in Patients with Cancer), LMWH was shown to be more effective than warfarin in reducing recurrent VTEs without a significantly increased risk of bleeding and the CONKO‐004 trial (Pilot Study of Intensified Chemotherapy and Simultaneous Treatment With Heparin in Outpatients With Pancreatic Cancer) demonstrated that LMWH reduced the incidence of symptomatic VTEs but did not affect progression‐free or overall survival .…”
Section: Pancreatic Cancer Disease‐related Complications and Managementmentioning
confidence: 99%
“…89 VTEs are another well established complication of advanced PDAC, with an incidence of ≥27%, which is 4 times higher than any other malignancy and 50 times higher than the average person. 90 Thrombosis, especially early, in patients with PDAC is a poor prognostic factor for early death. 91 Patients with PDAC have the highest rates of fatal pulmonary emboli, and VTEs are the second-leading cause of death.…”
Section: Pancreatic Cancer-related Symptom Managementmentioning
confidence: 99%
“…Pancreatic enzyme replacement and gastric acid suppression to prevent enzyme inactivation can strengthen nutrition and are recommended for patients with ongoing weight loss, abdominal cramping, or steatorrhea who are suspected of having enzyme deficiencies. Additionally, patients with pancreatic cancer are more prone to develop venous thromboembolic disease (11,12). Based on data from the CLOT and CONKO-004 studies—two large, prospective, randomized controlled trials—current guidelines recommend use of low molecular weight heparin, such as dalteparin or enoxaparin, instead of oral anticoagulants for the treatment of venous thromboembolism (VTE) (13,14).…”
Section: Goals and Challenges Of Palliative Care Integrationmentioning
confidence: 99%